Progress in research on mechanism of nicotinamide adenine dinucleotide and its precursors against aging-related diseases - Shixiong ZHENG; Jing LÜ; Shentao GUO; Xingfen YANG; Zhini HE (Editorial Office of Chinese Journal of Public Health, 2023)
Nicotinamide adenine dinucleotide (NAD+) is a coenzyme of various dehydrogenases, which plays an important role in physiological processes such as glycolysis and tricarboxylic acid cycle. In addition, NAD+ involves in various biological processes, such as energy metabolism, protein translation and protein modification, DNA repair and cellular stress to combat diseases. Numerous studies have shown that organismal aging is accompanied by decline of NAD+ levels, which is causally related to many aging-related diseases, including metabolic diseases, neurodegenerative diseases, immune inflammation, and tumors. Besides, NAD+ and its synthetic precursors (nicotinic acid, nicotinamide mononucleotide, nicotinamide ribose, etc.) have important efficacy in delaying aging and preventing many aging-related diseases. In this paper, we review regulatory mechanisms in reversing the age-dependent decline of NAD+ to prevent aging-related diseases, and briefly describe NAD+ metabolism, NAD+ precursor function, and effective NAD+ supplementation pathways for the prevention and treatment of aging-related diseases.